Implementasi Pelayanan Konseling Holistik Terintegrasi Aspek Teologi, Psikologi dan Skill Konseling - Joko Santoso (SANCTUM DOMINE: JURNAL TEOLOGI, 2020)
Services in the Field of Counseling to the community in the current era of mileniel, become a vital need in providing answers to the handling and resolution of multi-dimensional conflicts that occur amid modern society. The complexity of the problems of human life has reached a peak in all aspects and joints of life. Moreover, there are changes that occur in all fields of science that are growing rapidly along with the development of the era and the flow of information. Therefore the need for counseling guidance services to the community increasingly demands a better, comprehensive, integrated handler to meet and respond to the needs of the times.